2013
DOI: 10.1007/s00253-013-5407-7
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of PhbR, the transcriptional activator of polyhydroxybutyrate synthesis, by iron and the sRNA ArrF in Azotobacter vinelandii

Abstract: Azotobacter vinelandii is a Gram-negative bacterium able to synthesize poly-β-hydroxybutyrate (PHB), a biodegradable plastic of industrial interest. The phbBAC operon encodes the enzymes of PHB synthesis and is activated by the transcriptional regulator PhbR and the sigma factor RpoS. Iron limitation has been previously reported to increase PHB accumulation in A. vinelandii; however, the mechanism by which iron controls PHB synthesis is unknown. Under iron starvation in Escherichia coli, the RyhB sRNA modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…The posttranscriptional regulation of PHA (including PHB), however, has been reported in only a single species. In the gammaproteobacterium Azotobacter vinelandii, PHB synthesis was previously demonstrated to be under the control of the posttranscriptional regulatory cascade Gac/Rsm (47) and also negatively regulated by the activity of the ironresponsive small RNA ArrF (48)(49)(50). The S. meliloti genomes, however, lack genetic elements of the Gac/Rsm type (51), and there is no evidence for sequence or structural homology between A. vinelandii ArrR and S. meliloti MmgR RNAs or their flanking genes.…”
Section: Discussionmentioning
confidence: 99%
“…The posttranscriptional regulation of PHA (including PHB), however, has been reported in only a single species. In the gammaproteobacterium Azotobacter vinelandii, PHB synthesis was previously demonstrated to be under the control of the posttranscriptional regulatory cascade Gac/Rsm (47) and also negatively regulated by the activity of the ironresponsive small RNA ArrF (48)(49)(50). The S. meliloti genomes, however, lack genetic elements of the Gac/Rsm type (51), and there is no evidence for sequence or structural homology between A. vinelandii ArrR and S. meliloti MmgR RNAs or their flanking genes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, and over the past few years, it has been revealed that bacterial iron-regulated sRNAs have important modulating roles (e.g., in iron homeostasis) according to the levels of this essential and potentially toxic micronutrient [ 63 , 133 , 134 ]. The genes that encode for these small RNAs hold in their promoter regions the conserved Fur or iron boxes, which function as binding sites of the ferric uptake repressor (Fur) [ 130 , 133 , 134 , 135 , 136 ].…”
Section: Rna-mediated Control In Native Synthesis Of Phasmentioning
confidence: 99%
“…On the contrary, when iron is scarce, RNA polymerase is able to access the promoters of these genes, resulting in their transcription [ 130 , 133 , 134 , 135 , 136 ] ( Figure 3 A). In A. vinelandii, iron regulates the accumulation of PHB through one of these sRNAs, ArrF, while the mechanism seems to vary between different genetic backgrounds [ 63 , 124 , 130 , 137 ]. Muriel-Millan et al [ 63 ] reported that, under iron limitation, the ArrF sRNA acts as a positive post-transcriptional regulator of the phbR gene.…”
Section: Rna-mediated Control In Native Synthesis Of Phasmentioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido, si bien sería posible a priori especular que los cambios en la expresión de los genes cuyos productos están involucrados en la constitución de los gránulos de PHB sean consecuentes a una desregulación metabólica primaria originada por Sm8 que deriva en una mayor acumulación del polímero, el hallazgo de la regulación de los mensajeros de phaR, phaZ y phaP2 (que precisamente PhaR regula, tal como se extrapola a partir de lo descripto del estudio de genes homólogos) en condiciones de crecimiento exponencial en las que no se han generado aún reservas de PHB, eleva la sospecha acerca de una posible regulación primaria de estos genes mediada por el sRNA. En relación a esta última hipótesis, se ha descripto que el sRNA ArrF en la gama-proteobacteria Azotobacter vinelandii capaz de regular de forma directa la traducción del ARN mensajero del gen homólogo de phaR en esa especie (Pyla, et al, 2009, Pyla, et al, 2010, Muriel-Millan, et al, 2014. Dado que no existe evidencia alguna de homología entre los ARNs ArrF y Sm8, eventos evolutivos independientes y análogos podrían haber conducido a establecer la regulación a nivel post-transcripcional del gen phaR mediada por un sRNA.…”
Section: Smc00777 Phap1unclassified